2e-3=1

Simple and best practice solution for 2e-3=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2e-3=1 equation:


Simplifying
2e + -3 = 1

Reorder the terms:
-3 + 2e = 1

Solving
-3 + 2e = 1

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 2e = 1 + 3

Combine like terms: -3 + 3 = 0
0 + 2e = 1 + 3
2e = 1 + 3

Combine like terms: 1 + 3 = 4
2e = 4

Divide each side by '2'.
e = 2

Simplifying
e = 2

See similar equations:

| (4-9w)/(4w^2-49) | | 7c-5=9 | | 4x+25=19 | | 4-9w/4w^2-49 | | 11/10d=2/5 | | 48x+7.48=-5 | | 5a+1=9 | | (2x^3-3x^2-18x-8)/x-1) | | 15x-28=73 | | 18=15+5x | | 7p^2-7p-24=-5 | | 16t^2-23t-2= | | 3.3+9.8=19.04 | | 5/11g=2/3 | | n-5/n+8=2/7 | | X+68=x+128 | | 3m^2+6m-12m^2+9m= | | (2x^3+3x^2)+(5x^3+4x^2)= | | 21=3-9x | | 4v^2-12v-14=-11 | | z/1.3=.02 | | 7n+4=45 | | M^2+121=0 | | (0.25)x+2=64 | | L=34x+0.5 | | 5t^2-11t-3= | | 9+5x=-11+x | | s/4=6/7 | | 2(1-2x)=-3 | | 7z-6=6 | | 14-x=28 | | 1/2.4/7 |

Equations solver categories